THE MADRID PROTOCOL: MEWUJUDKAN PERLINDUNGAN HUKUM YANG EFEKTIF BAGI MEREK TERKENAL DI ASEAN - Rohaini, Rohaini (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
Intellectual Property Rights protection system is territorial. Registration and law enforcement must be done separately in each relevant jurisdiction. In the brand regime, this system is often a challenge for brand law enforcement. In practice, a brand with a well-known trademark often used without permission even registered by an unauthorized party only because the trademark is not registered in that country. Even this condition occurs in the ASEAN region. Take Vietnam, for example, in Vietnam it would be very easy to find the use of famous brands without permission by certain parties very freely because the trademark was not registered in Vietnam. The Madrid Protocol, which is a refinement of the Madrid Agreement, since its inception in 1989 is an alternative in building an international registration system. This system offers convenience for brand owners to get protection for their brands worldwide (Protocol member countries) with only one application and one procedure through WIPO International Berau to proceed to destination countries